Class profile and prevalence of overweight and obesity in adolescents - pilot study on the "Health Steps" project - Agnieszka Białek-Dratwa; Elżbieta Szczepańska; Małgorzata Słoma-Krześlak; Wiktoria Staśkiewicz-Bartecka; Sylwia Jaruga-Sękowska; Justyna Nowak; Joanna Nieć-Leśniak; Olga Sobek; Agata Kiciak; Agnieszka Bielaszka; Oskar Kowalski (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: The study aimed to assess the prevalence of overweight and obesity in adolescents aged 11-13 and compare the body weight and body fat content of students in general and sports classes. Material and methods: The pilot study involved 352 pupils in grades 6 and 7 from primary schools in Bytom, participating in the project "Health Steps - education and learning as a determinant of a healthy and open society". The study was meticulously conducted, with careful attention to detail and consideration of the class profile. A sports class, implementing 10 hours of physical education per week, was compared to a general class with 4 hours. To ensure the accuracy of the results, body composition was assessed using bioelectrical impedance analysis (BIA), a widely accepted method. Polish centile grids, a reliable tool, were used to assess body mass index (BMI). Age and gender-specific norms for adolescents were also employed to assess normal body fat, further enhancing the study's validity. Results: In the general profile classes, 77 (25.58%) pupils were overweight, including 36 (22.78%) girls and 41 (28.67%) boys. In sports profile classes, it affected 8 (15.69%) pupils, including 2 (10.53%) girls and 6 (18.75%) boys. In the sports classes, obesity did not occur, while in the general profile classes it affected 13 (4.32%) pupils, including 6 (3.80%) girls and 7 (4.90%) boys. Regarding body fat percentage, 56 (15.91%) students were overweight. Conclusions: The study's key findings reveal that over 25% of adolescents have excessive body weight, with overweight and obesity being less common among pupils in sports classes. Furthermore, over 30% of children have excessive body fat. Notably, girls in sports classes were less likely to be overweight and obese than girls in general profile classes. However, the differences in body fat among boys in the sports and general classes were not statistically significant.